If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60x + 40 = 700 Reorder the terms: 40 + 60x = 700 Solving 40 + 60x = 700 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 60x = 700 + -40 Combine like terms: 40 + -40 = 0 0 + 60x = 700 + -40 60x = 700 + -40 Combine like terms: 700 + -40 = 660 60x = 660 Divide each side by '60'. x = 11 Simplifying x = 11
| 60+40=700 | | x^2+x+9=(3x+2)(x-8) | | 35x+25=700+40 | | 6+3c=38-c | | 7x+3=6x+26 | | f(x)=5x^3+15x^2-120x | | 5x+5-6x=2x+17-7x | | 35x(25+40)=700 | | 9y+7=31+y | | y-2=-3(x-5) | | 100+80t+4b= | | 34.7x+40.9+38.8x+18.8= | | 4x+6-2x=2(x-3) | | -4x^2-12x-10=0 | | x(x+4)=-84 | | 7x^2-36x+6=0 | | 3x(x-1)+15=7 | | 40+2y-16=11y-11-4y | | 1223423123x=213123123 | | -3x+18=-10x+4 | | 3x+9=5x-19 | | 6(2.5)+3y=12 | | (3x)(3x-2)(x)=540 | | 0=0.3x^2+2x-50 | | x-55=10 | | 2q^3-5q^2-500=0 | | 42-n*n=n | | 1996+43x=0 | | log(10)x+log(10)x-1=log(10)30 | | -24+11=5x+3-4x | | .10(c+3)=-12 | | log(x)+log(x-1)=log(30) |